Konsep Kepemimpinan Bermutu dalam Pendidikan Islam - Aldo Redho Syam (At-Ta'dib, 2017)
Leaders in Islamic educational institutions have a great responsibility, because of their role such as the ability to make decisions and skills in making new ideas as the demands of society. Being a leader in Islamic educational institution is not only required to master various leadership theories, but also must be able to apply them in the institution. Some principles that must be owned by a leader in carrying out his leadership in an Islamic educational institution should rely on things that have been ordered by Allah SWT. Principles of leadership in Islam namely trust, fair, deliberation, and amar ma ' ruf nahi munkar. While qualifications of leader in Islamic education as follows: sincere, always take the initiative, able to create network and use it, trustworthy, work hard and earnest, mastering the problem and can solve it, have high integrity, have high guts and not afraid of risk, honest and open, ready to sacrifice, assertive, intelligent in seeing, listening, evaluating, judging, deciding, and solving it, able to communicate, and Good in mu'amalah.